Sigesbeckia orientalis L. Derived Active Fraction Ameliorates Perioperative Neurocognitive Disorders Through Alleviating Hippocampal Neuroinflammation - Chu, John Man Tak; Abulimiti, Amina; Wong, Brian Shing Hei; Zhao, Guan Ding; Xiong, Shi Hang; Zhao, Ming Ming; Wang, Yingyi; Chen, Ying; Wang, Jiaqi; Zhang, Yan; Chang, Raymond Chuen Chung; Yu, Hua; et al. (Frontiers in Pharmacology, 2022)
Neuroinflammation is closely related to the pathogenesis of perioperative neurocognitive disorder (PND), which is characterized by the activation of microglia, inflammatory pathways and the release of inflammatory mediators. Sigesbeckia orientalis L. (SO) is a traditional Chinese medicine which demonstrates anti-inflammatory activities in different models. In this study, we aim to isolate an active fraction from the extract of SO with higher potential of anti-inflammation and confirm if the selected fraction exerts neuroprotection in PND animal model. Moreover, the components in the selected fraction are determined by UPLC-PDA analysis. Three fractions were prepared by column chromatography packed with three different macroporous resins. Anti-inflammatory activities of prepared fractions were accessed in microglial BV2 cultures by nitric oxide release, gene expression of inflammatory cytokines and activation of inflammatory JNK and NF-kB pathway molecules. Our results demonstrated that the fraction prepared from D101 macroporous resin (D101 fraction) exhibited a more potent anti-neuroinflammatory effect. The neuroprotective effect of D101 fraction was further examined in postoperative mice. Our results showed that surgery-induced cognitive dysfunction was attenuated by D101 fraction treatment. D101 fraction also reduced microglial activation, inflammatory cytokines and inhibiting JNK and NF-kB pathway molecules in the hippocampus. Furthermore, surgery induced dendritic spine loss while D101 fraction ameliorated the spine loss in the hippocampus. For safety concern, anti-thrombotic effect was examined by tail bleeding assay and no significant change of the bleeding pattern was found. UPLC-PDA analysis indicated that flavonoids (rutin, isochlorogenic acid A, isochlorogenic acid C) and terpenoid (darutoside) were the most important components in the D101 fraction. Our results support a therapeutic, as well as the translational potential for D101 fraction in ameliorating postoperative neuroinflammation and subsequent PND in the clinical setting without increasing bleeding tendencies.